Safety, Efficacy, and Effectiveness of Maternal Vaccination against Respiratory Infections in Young Infants - Makan-Murphy, Nisha; Madhi, Shabir A; Dangor, Ziyaad (Seminars in Respiratory and Critical Care Medicine, 2024)
Lower respiratory tract infection (LRTI) is a major cause of neonatal morbidity and mortality worldwide. Maternal vaccination is an effective strategy in protecting young infants from LRTI, particularly in the first few months after birth when infant is most vulnerable, and most primary childhood vaccinations have not been administered. Additionally, maternal vaccination protects the mother from illness during pregnancy and the postnatal period, and the developing fetus from adverse outcomes such as stillbirth and prematurity. In this paper, we review the safety, efficacy, and effectiveness of maternal vaccines against LRTIs, such as pertussis, influenza, coronavirus disease 2019, and respiratory syncytial virus.
Keywords: pregnancy; vaccination; safety; immunogenicity; respiratory pathogens